Catheter replacement structure in home medical care settings and regional characteristics in Tokyo and three adjoining prefectures. Issue 4 (21st June 2016) - Kimura, Takuma; Yoshie, Satoru; Tsuchiya, Rumiko; Kawagoe, Shohei; Hirahara, Satoshi; Iijima, Katsuya; Akahoshi, Toru; Tsuji, Tetsuo
Abstract : Aim: The present study investigated the association between the structure of catheter replacement services in home medical care settings and regional characteristics. Methods: An anonymous self‐administered questionnaire was carried out from August to September 2013. Participants were physicians from 5338 clinics that provided medical care services at home, and nurses from 1619 home‐visit nursing stations in Tokyo and three adjoining prefectures. The questionnaire covered catheter replacement (gastrostomy tubes, nasogastric tubes, tracheal cannulas) during home medical care, and the professions of those who replaced urethral catheters for male and female patients. Regions were divided into two groups (higher‐ and lower‐density regions) based on the number of clinics, number of home‐visit nursing stations and the ratio of the population aged ≥65 years. The rates of respondents that reported catheter replacement was usually executed, and those who reported catheters were replaced by "physicians in principle" were compared between the groups. Results: Responses were received from 842 clinics (16.3%) and 499 home‐visit nursing stations (31.4%). In the higher‐density regions, the rate of physicians who reported urethral catheters for male patients were replaced by "physicians in principle" was significantly higher than in the lower‐density regions ( P  < 0.001). In the lower‐density regions, the rate of nurses who reported urethral catheters for male patients were replaced by "nurses in principle" was significantly higher compared with the higher‐density regions ( P  < 0.016). Conclusions: In home medical care settings, urethral catheters for male patients are replaced by nurses in regions where physician resources are limited.Geriatr Gerontol Int 2017; 17: 628–636 .